Quantification of timelapse 3D tumor spheroid killing activity of NK cells using a live-cell imaging system - Jakkrapatra Srisantitham; Nontaphat Thongsin; Siriwal Suwanpitak; Methichit Wattanapanitch (PLoS ONE, 2025)
Natural killer (NK) cells are critical components of the immune system, responsible for recognizing and eliminating a wide range of abnormal cells, including those infected by pathogens or transformed into cancerous cells. Their potent cytotoxic functions, encompassing the direct release of cytotoxic granules, antibody-dependent cell cytotoxicity (ADCC), and the expression of apoptosis-inducing ligands, make NK cells a promising therapeutic product in cancer immunotherapy. This study presents a detailed protocol for assessing NK cell-mediated cytotoxicity against three-dimensional (3D) tumor spheroids using a live-cell imaging system, offering a more physiologically relevant model compared to traditional 2D cultures. Utilizing this 3D spheroid model, we explored the dynamics of NK cell killing activity against two aggressive solid cancer cell lines, cholangiocarcinoma (KKU-213A) and triple-negative breast cancer (MDA-MB-231), across varying effector-to-target (E:T) ratios. Our findings reveal a dose-dependent increase in NK cell activity, with higher E:T ratios yielding more pronounced tumor cell death. Real-time imaging further demonstrated distinct differences in the morphology and cell death patterns of the two cell lines, with MDA-MB-231 cells exhibiting a faster response to NK cell cytotoxicity. These findings underscore the utility of 3D spheroid models and live-cell imaging for studying NK cell function and advancing the development of NK cell-based immunotherapies. The standardized protocol detailed herein provides a valuable insights into immune surveillance and therapeutic applications.